Emergent Pulmonary Embolectomy and Advanced Glioblastoma Multiforme - Michael S. Firstenberg; Danielle Blais; Erik Abel; Herbert B. Newton; Juan Crestanello (Case Reports in Medicine)
Pulmonary emboli are frequent causes of morbidity and mortality in patients with brain tumors. Treatment options are limited in these complex patients. We report a case of successful acute pulmonary embolectomy in a patient with an advanced brain cancer.